Adaptation of a gender-transformative sexual and reproductive health intervention for adolescent boys in South Africa and Lesotho using intervention mapping. Issue 1 (1st January 2021) - Aventin, Áine; Rabie, Stephan; Skeen, Sarah; Tomlinson, Mark; Makhetha, Moroesi; Siqabatiso, Zanele; Lohan, Maria; Clarke, Mike; Lohfeld, Lynne; Thurston, Allen; Stewart, Jackie
ABSTRACT: Background : Rates of adolescent HIV and unintended pregnancy in southern Africa are amongst the highest in the world. Gender-transformative interventions that address underlying gender inequalities and engage both males and females have been emphasised by the World Health Organisation, amongst others, to target prevention. However, few such gender-transformative interventions have been rigorously developed or evaluated. Objective : To expedite potential impact and reduce development costs, we conducted a needs assessment to inform the co-design, in consultation with local stakeholders, of adapted versions of an existing gender-transformative Relationships and Sexuality Education intervention for use in South Africa and Lesotho. Methods : Adaptation of the intervention was guided by a modified version of Intervention Mapping (IM). This process involved consultation with separate adolescent, community and expert advisory groups and a collaboratively conducted needs assessment, which drew on focus groups with adolescents (8 groups, n = 55) and adults (4 groups, n = 22) in South Africa and Lesotho, and was informed by our systematic review of the literature on the determinants of condom use among adolescents in the region. Results : The findings clarified how the intervention should be adapted, which individual- and environmental-level determinants of condom use to target, and actions for facilitating successful adoption, evaluation and implementation in the new settings. Conclusions : The IM approach allows for a systematic appraisal of whether components and processes of an existing intervention are appropriate for a new target population before costly evaluation studies are conducted. The findings will be of interest to those wishing to rigourously develop and evaluate gender-transformative interventions engaging men to improve health for all.